History in contemporary art and culture - O'Kane, Paul (Routledge, 2023)
"This unique book offers guidance for Contemporary Art practices in dialogue with history, story, memory and tradition. Artist and Lecturer Paul O'Kane uses innovative and creative means, informed by a storytelling tradition as well as academic research, to make connections between contemporary art, history and the past. The aim of this book is to give readers a sense of the profundity of historical questions, while making the challenge inviting, welcoming and manageable. It is designed to set out an expansive, inclusive and diverse range of potential directions and speculations, from which students can develop personal paths of enquiry. This is achieved by writing and designing the text in an accessible way and providing a range of 'ways-in': series of carefully chosen references, examples, key texts and possible essay questions are chosen and pitched at various levels and can be close-read, discussed, digested, and responded-to either verbally or in the form of a presentation or essay. Written for a broad range of fine arts students, this book encourages readers to reconsider their studies and art practices in light of a historical perspective enhanced by creative contributions from artists, imaginative philosophers and influential cultural commentators"--Provided by publisher.